Furlough and Household Financial Distress during the Covid-19 Pandemic - Christoph Görtz; Danny McGowan; Mallory Yeromonahos (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study how furlough affects household financial distress during the COVID-19 pandemic. Furlough increases the probability of late housing and bill payments by 30% and 9%, respectively. The effects exist for individuals who rent their home, but not mortgagees who can mitigate financial distress by reducing expenditure during furlough by deferring mortgage payments though the Mortgage Holiday Scheme. Furloughed individuals significantly reduce expenditure and spend their savings to offset furlough-induced income reductions. This creates wealth inequality but lowers the probability a furloughed worker experiences financial distress after returning to work. Estimates show an 80% government contribution to furloughed workers' wages minimizes the incidence of financial distress at the lowest cost to taxpayers.
Keywords: D14; D31; E24; G51; H24; 330; furlough; short-time work; Coronavirus job retention scheme; Covid-19 pandemic; financial distress; automatic stabilizers; inequality